Evaluation of Pentraxin-3 and Interleukin-6 Levels in Serum and Gingival Crevicular Fluid in Patients with Generalized Periodontitis and Periodontal Health Controls before and after Scaling and Root Planing - Siamak Yaghobee; Sadegh Hasannia; Fatemeh Hamidzadeh; Saman Valadan Tahbaz; Rojin Shahmohammadi; Farzaneh Poursafar (Frontiers in Dentistry)
Objectives: Pentraxin-3 (PTX3) and interleukin-6 (IL-6) are two of the most important inflammatory cytokines produced by cells in periodontal tissues. The present study aims to evaluate the levels of PTX3 and IL-6 in serum and gingival crevicular fluid (GCF) in patients with generalized periodontitis stages II and III, grades A and B, and periodontal health individuals before and after scaling and root planing (SRP).